Using superabsorbent polymers in high performance concrete to mitigate autogenous and plastic shrinkage while observing the compressive strength - Ebrahim, Nuraan (Stellenbosch : Stellenbosch University, 2017)
Thesis (MscEng)--Stellenbosch University, 2017.